Laksamana Cheng Ho's Contribution in the Early Spread of Islam in Sunda land 1405-1433 - Syah, M. Kautsar Thariq; Sa'adah, Putri Lailatus; Nurcahya, Yan; Maulana, Ilham; Sidik, Mohammad Dindin Hamam (El Tarikh : Journal of History, Culture and Islamic Civilization, 2025)
This article discusses Admiral Cheng Ho's visit to the Sundanese region, which coincided with the initial process of Islamization in West Java. This study highlights the role of Cheng Ho's expedition that is often overlooked in the spread of Islam in the archipelago, particularly in the Sunda region. The research uses historical research methods by collecting data obtained in libraries from various documentary sources such as books, journals, and relevant writings related to Islam and the global historical context. Although Admiral Cheng Ho's stopover at Muarajati Port lasted only seven days, it had a lasting cultural and religious impact. His entourage included Sheikh Hasanudin bin Yusuf Shidik who later became known as Sheikh Quro who introduced the teachings of the Qur'an to the locals. Cheng Ho's presence contributed to the development of various sectors including agriculture, trade, architecture, and cultural arts. Some of his followers even settled permanently by marrying the locals. This research contributes to filling the reference gap regarding the history of Islamization in the Sundanese region, especially the involvement of the Chinese Muslim community.